Feline Coronaviruses: Pathogenesis of Feline Infectious Peritonitis - Tekes, G; Thiel, H-J (Advances in virus research, 2016)
Feline infectious peritonitis (FIP) belongs to the few animal virus diseases in which, in the course of a generally harmless persistent infection, a virus acquires a small number of mutations that fundamentally change its pathogenicity, invariably resulting in a fatal outcome. The causative agent of this deadly disease, feline infectious peritonitis virus (FIPV), arises from feline enteric coronavirus (FECV). The review summarizes our current knowledge of the genome and proteome of feline coronaviruses (FCoVs), focusing on the viral surface (spike) protein S and the five accessory proteins. We also review the current classification of FCoVs into distinct serotypes and biotypes, cellular receptors of FCoVs and their presumed role in viral virulence, and discuss other aspects of FIPV-induced pathogenesis. Our current knowledge of genetic differences between FECVs and FIPVs has been mainly based on comparative sequence analyses that revealed "discriminatory" mutations that are present in FIPVs but not in FECVs. Most of these mutations result in amino acid substitutions in the S protein and these may have a critical role in the switch from FECV to FIPV. In most cases, the precise roles of these mutations in the molecular pathogenesis of FIP have not been tested experimentally in the natural host, mainly due to the lack of suitable experimental tools including genetically engineered virus mutants. We discuss the recent progress in the development of FCoV reverse genetics systems suitable to generate recombinant field viruses containing appropriate mutations for in vivo studies.